EVIDENCE BASED LEARNING: AN ANALYSIS OF IMPACT OF EXPERIENTIAL LEARNING ON ATTAINMENT OF INTENDED SPECIFIC LEARNING OUTCOME - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2021)
The intension of the present study is to enhance the conceptual understanding amongst Grade 12 School students. As a teacher, it is very challenging to make the learners to be strong and have deep understanding in the theoretical concept for its application in day- to-day life. The experiential learning activities enhance the deep learning. The purpose of the study is to investigate the effect of experiential learning activities designed for the concept “corrosion” on the academic performance amongst Senior Secondary School students in Chemistry. Totally 40 students participate in the study. The samples are drawn using Purposive sampling technique. The samples are divided in to two groups: study and the control group based of their performance of formative assessment before the treatment. Students of the study group are taught by using experiential learning activities. The present study is experimental in nature. Data is collected using formative assessment before and after the treatment. Mean, mean difference and standard deviation are the statistical tools applied to analyze the data. Results of the study reveal that experiential learning activities have a positive impact on the deep conceptual understanding to achieve the intended specific learning outcome. Based on the results few recommendations are made.